ANALISIS BIAYA DAN WAKTU PELAKSANAAN PELEBARAN PERKERASAN JALAN (Jurnal Spesialis Teknik Sipil (JSpTS), 2021)
Roads are a very important need because they can support several fields in the area, which include the economic, social and tourism fields. In supporting these needs, the DPU. Bina Marga has issued references as guidelines for the implementation of planning, which include 02/M/BM/2013, Pd T-05-2005 and Pt T-01-2002-B. According to the Government Regulation of the Republic of Indonesia No. 34 of 2006 the province has a lane width of at least 7 (seven) meters. The road leading to Bts City Bojonegoro-Pajeng (Bts. Nganjuk Regency) is currently appropriate pavement structure for repairs on Jalan Departemen Bojonegoro–Pajeng (Bts. Nganjuk Regency) (Link 144) Km. B.Goro 6+000 – 10+000 in Bojonegoro Regency is a structure using asphalt concrete pavement (flexible pavement) because it relates to a shorter work execution time of 196 calendar days with a budget of Rp. 11,693,000,000,-. while for rigid pavement (Rigid Pavement) the required time is 306 calendar days with a budget of Rp. 16,485,199,000, - this will risk the project not being completed or breaking the contract, because most APBD projects are single year or only one budget year. So alternative 1 is very possible to implement, with the work item Overlaying the old pavement using flexible asphalt (Flexible pavement) with AC WC 5 cm thick, while for the widening work it is a sub-base layer using Class A Aggregate with a thickness of 30 cm, for asphalt work: asphalt foundation (AC Base) with a thickness of 14.5 Cm, intermediate asphalt (AC BC) with a thickness of 6 Cm medium for the top layer (AC WC) with a thickness of 5 Cm, and it is recommended that in planning laboratory data and other data used must really be implemented because it is the main determinant in planning calculations. only 6 m wide. less than 7 m. Based on the results of the analysis, it can be concluded that the